Identification of Key Competences in Management Through Visual Representation of Keywords Using Vosviewer - Lukas VARTIAK; Galina JASECKOVA; Stephan STIEGLAUER (Communications of International Proceedings, 2023)
The paper aims to identify a set of key competences that are important for managerial practice. We divided the paper into four main parts: introduction and theoretical background, methodology, results and discussion, and conclusion. The first part defines key skills, key competences and key qualifications, and the second part addresses the methodology. The third part identifies a resource, relationship, change, and skill as a set of essential competences that are important for management. VOSviewer software was used as the primary research method. It analyses journals, researchers, or individual publications, and they can be built based on citation, bibliographic coupling, co-citation, or co-authorship relations. In the last part of the paper, we also express the ambition to continue this research by identifying the intersections of critical thinking and management.
Keywords: management; key competences; skills; qualifications; VOSviewer